Validating an instructional competency model for assistant headteachers: Preliminary evidence from a pilot study using CFA and SEM - Erna Suwardi; Muhamad Suhaimi Taat; Roslee Talip; Mohd Sobrye Paimin (Global Academic Excellence, 2025)
This study aimed to develop and validate an Instructional Competency Model tailored for Assistant Headteachers (GPK) in Malaysian primary schools, across both rural and urban school settings in Sabah. Grounded in the KOMPAS 2.0 framework, the model conceptualized instructional competency as a multidimensional construct comprising four latent domains: Curriculum Focused Instructional Leadership (IBK), Research Culture (PP), Holistic Monitoring (PM), and Digital Ecosystem Culture (PED). A pilot survey involving 100 GPK across various districts in Sabah was conducted. The sample comprised 58 respondents from rural schools and 42 from urban schools, with balanced demographic characteristics. Data were analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to assess construct validity and model fit. The CFA results demonstrated excellent fit indices (χ²/df = 0.446, CFI = 1.000, RMSEA = 0.041), with standardized factor loadings ranging from 0.80 to 0.87. All constructs achieved strong composite reliability and average variance extracted. SEM analysis confirmed significant path coefficients from the main construct to its four dimensions, with Curriculum Focused Instructional Leadership (β = 0.87) emerging as the strongest contributor. These results confirm the robustness and contextual relevance of the model, while acknowledging the limitations of a pilot study. The validated model contributes theoretical novelty by extending instructional leadership theory into middle leadership domains and by adapting KOMPAS 2.0 specifically for Assistant Headteachers. It offers a practical framework that can be applied within Malaysia and in comparable international contexts, providing insights for education policymakers, school administrators, and training providers.